Analysis of Passenger Response to Service Quality Terminal 1 Juanda Airport Surabaya - Anggun Surya Mutiara Indah; Muhammad ikhsan Setiawan (Journal of World Conference (JWC), 2020)
Juanda Airport Surabaya is one of the airports managed by PT Angkasa Pura 1 (Persero). Airline LCC or Low Cost Carrier is an airline that offers low rates to its customers, with the consequence of eliminating or reducing some services or facilities that will be obtained by regular flights. This study aims to analyze the Facilities / Infrastructure, Accessibility & Public Facilities on the quality of service providers, in Terminal 1 of Juanda Airport Surabaya and analyze the LCC ( Low Cost Carrier ) airline in Terminal 1 of Juanda Airport Surabaya. This research includes quantitative research, using questionnaires as a data collector, the sample used is 100 passengers from various airlines in the research location, namely in Terminal 1 Juanda Airport, Surabaya. Data analysis using multiple linear regression analysis and hypothesis testing include t test, f test and multiple determination. Based on the results of the study concluded the quality of passenger services (Facilities/Infrastructure, Accessibility & Comfort and Safety) to the performance of managers, in Terminal 1 Juanda Airport Surabaya is quite good and adequate. This was proven by the answers of 100 respondents who stated that accessibility, facilities and infrastructure and comfort and safety in Juanda Airport Terminal 1 responded well. Based on the results of calculations there is the influence of facilities / infrastructure, accessibility & comfort and safety of service quality.